Calreticulin is a B cell molecular target in some gastrointestinal malignancies - Pekáriková, A; Sánchez, D; Palová-Jelínková, L; Simsová, M; Benes, Z; Hoffmanová, I; Drastich, P; Janatková, I; Mothes, T; Tlaskalová-Hogenová, H; Tucková, L (Clinical and experimental immunology, 2010)
Calreticulin, upon translocation to the cell surface, plays a critical role in the recognition of tumour cells and in experimentally induced cellular anti-tumour immunity. However, less is known about anti-calreticulin antibodies and their role in malignancies. Using enzyme-linked immunosorbent assay (ELISA), we found immunoglobulin (Ig)A and/or IgG anti-calreticulin antibodies in sera of approximately 63% of patients with hepatocellular carcinoma (HCC), 57% of patients with colorectal adenocarcinoma (CRA) and 47% of patients with pancreatic adenocarcinoma (PACA), while healthy controls, patients with viral hepatitis C and with chronic pancreatitis reached only 2%, 20% and 31% seropositivity, respectively. We found significantly elevated mean levels of IgA anti-calreticulin antibodies (P < 0.001) in patients with HCC (78.7 +/- 52.3 AU, mean +/- standard deviation), PACA (66.5 +/- 30.9 AU) and CRA (61.8 +/- 25.8 AU) when compared to healthy controls (41.4 +/- 19.2 AU). Significantly elevated mean levels of IgG anti-calreticulin antibodies (P < 0.001) were detected in patients with HCC (121.9 +/- 94.2 AU), gall bladder adenocarcinoma (118.4 +/- 80.0 AU) and PACA (88.7 +/- 55.6 AU) when compared to healthy controls (56.7 +/- 22.9 AU). Pepscan analysis revealed a large number of antigenic epitopes of calreticulin recognized by both IgA and IgG antibodies of patients with HCC and PACA, indicating robust systemic immune response. Moreover, significantly elevated levels of antibodies against peptide KGEWKPRQIDNP (P < 0.001) in these patients, tested by ELISA, confirmed the distinct character of antibody reactivity against calreticulin. The high occurrence and specificity of serum anti-calreticulin autoantibodies in the majority of patients with some gastrointestinal malignancies provide the evidence for their possible clinical relevance.
Keywords: Young Adult; nádorové proteiny; Immunoglobulin G; Hepatitis C, Chronic; Male; kolorektální nádory; Gallbladder Neoplasms; Autoantibodies; mladý dospělý; Pancreatitis; Epitopes; B-lymfocyty; Adult; kalretikulin; Carcinoma, Hepatocellular; pankreatitida; protilátky nádorové; dospělí; epitopy; imunoglobulin G; senioři; nádory žlučníku; mužské pohlaví; lidé středního věku; Aged; Antibodies, Neoplasm; Autoantigens; autoantigeny; ELISA; Pancreatic Neoplasms; Calreticulin; senioři nad 80 let; Enzyme-Linked Immunosorbent Assay; Antibody Specificity; lidé; specificita protilátek; ženské pohlaví; adenokarcinom; Humans; autoprotilátky; nádory slinivky břišní; chronická hepatitida C; hepatocelulární karcinom; imunoglobulin A; Aged, 80 and over; Neoplasm Proteins; Colorectal Neoplasms; B-Lymphocytes; Adenocarcinoma; Liver Neoplasms; Female; Immunoglobulin A; nádory jater; Middle Aged